Association between Systemic Lupus Erythematosus and Periodontitis: A Systematic Review and Meta-analysis - Rutter-Locher, Zoe; Smith, Toby O.; Giles, Ian; Sofat, Nidhi (Frontiers in Immunology, 2017)
Background: Systemic Lupus Erythematosus (SLE) is a chronic systemic inflammatory autoimmune disease, the aetiology of which remains only partially characterised. Strong evidence implicates chronic infections in the development and chronicity of autoimmune conditions. Recently, an association has been demonstrated between periodontitis and rheumatoid arthritis. Such observations have led to the investigation of the possible role of periodontitis and oral dysbiosis in other systemic inflammatory conditions, including SLE. The aim of this study was to examine whether there is an association between SLE and periodontitis. Methods: MEDLINE via OVID, EMBASE via OVID, and PsycINFO via OVID databases were searched to identify eligible studies, screened by two independent authors and verified by a third. Studies comparing presence of periodontitis in SLE cases to controls without SLE were included. Data was extracted using a predefined table and papers were appraised using Down’s and Black tool. Mantel–Haenszel meta-analysis was performed using RevMan. Results: Eight case-control studies were included, with 487 SLE cases and a total of 1,383 participants. On meta-analysis of four studies, risk of periodontitis in SLE cases compared to controls was significantly greater with a risk ratio of 1.76 (95% CI 1.29-2.41, p=0.0004). No statistical difference was found in individual measures of periodontitis, such as probing depth or clinical attachment loss, between SLE cases and controls. Conclusion: Our study found a statistically significant increased risk of periodontitis in patients with SLE compared to controls. This finding suggests a possible association between these two conditions. Larger longitudinal studies are needed to confirm this possible association.